Estudio de prefactibilidad para la instalación de una planta productora de salsa a base de aceituna negra ascolana (Olea europaea L) - Misari Juarez, Pamela Camila (2023)
The following prefeasibility study sought to determine the feasibility of implementing a plant to produce a sauce based on black olives. The product was chosen because of the increasing demand for healthy products. A market study was carried out and it was determined that the target public is people between 18 and 55 years of age from socioeconomic levels A and B with an organic product consumption behavior. Subsequently, the specific demand for the project was calculated using segmentation criteria and adjustment factor. In addition, the plant location was determined, where the Ranking of factors method was used for macro- and micro-location, resulting in the department of Lima and the district of Lurin. In the next chapter it was determined that the capacity of the plant would be 152 293 containers of finished product, the bottleneck being the liquefaction process. Subsequently, the minimum area of the production zone was established through Guerchett's analysis, where 27,94 m2 was obtained, and considering the other zones, it was concluded that the total area of the plant is 225 m2. To evaluate the profitability of the project for 5 years, economic and financial cash flows were prepared and the NPV and financial IRR were calculated to determine the project's viability with a result of S/ 228 950 and 35% respectively. Finally, a social evaluation was carried out where the indicators of employability and return on capital were analyzed considering a WACC of 15,56% as the discount rate.